FOOD HABITS OF LUNDU FISH (Mystus gulio Hamilton, 1822) IN THE WATERS OF SUNGAI DUA (TWO RIVERS) VILLAGE, RAMBUTAN DISTRICT, BANYUASIN REGENCY, SOUTH SUMATERA - Ridho, Moh Rasyid; Patriono, Enggar; Pratiwi, Ria Hani (BIOVALENTIA: Biological Research Journal, 2019)
The research about food habits of Lundu fish (Mystus gulio Hamilton, 1822) in the waters of Sungai Dua (Two Rivers) Village, Rambutan District, Banyuasin Regency, South Sumatra. The sampling was conducted in five times in December 2016; January, February, March and April 2017. Identification of the samples was in Laboratory of Animal Taxonomy, Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, Indralaya.The purpose of the research was to analyze the food habits of Mystus gulio Hamilton, determine the relationship of length-weight, determine the conditions, analyze the gastric fullness index. The results of this research showed that the food habits of Mystus gulio Hamilton is plankton, like Cyanophyta, Chlorophyta, Diatomae, Desmidiacae, Euglenophyta, Pyrrophyta, Ciliata, Rhizopoda, Rotaria, and Entomostraca.